Coexistence of anti-neurexin-3α-associated autoimmune encephalitis and systemic lupus erythematosus in an adult patient: a case report - Zhang, Huiting; Kong, Ning; Liao, Zhimin; Fu, Jiawu; Pan, Jiangang; Zhong, Wangtao (Frontiers in Immunology, 2025)
Autoimmune encephalitis (AE) associated with anti-neurexin-3α antibodies, an uncommon variant of AE, exhibits particularly low frequency when coexisting with systemic immune dysregulation. The heterogeneous clinical manifestations of this neuroinflammatory disorder hinder timely diagnosis. We describe a 55-year-old male diagnosed with anti-neurexin-3α-associated AE, complicated by systemic lupus erythematosus (SLE) and antiphospholipid antibodies. The case presented with pyrexia persisting for 3 days, followed by acute-onset vertigo and encephalopathy evolving over 7 h. The clinical course was marked by visual obscuration, cephalalgia with associated emetic episodes, and concurrent neuropsychiatric manifestations, including psychomotor agitation and urinary incontinence. Anti-neurexin-3α antibody was detected in the cerebrospinal fluid. The patient tested positive for anti-neutrophil cytoplasmic antibody, anti-SS-A/RO60KD, anti-SS-A/RO52, anti-SnRNP, and lupus anticoagulant. Plasma complement levels (C3 and C4) were decreased, while elevated titers were observed for antinuclear antibodies, anti-double-stranded DNA, and anti-β2 glycoprotein I IgG antibodies. Immunomodulatory therapy with pulse methylprednisolone and intravenous immunoglobulin infusion elicited marked neurological recovery. This case underscores the imperative to investigate AE in the differential diagnosis of acute neuropsychiatric decompensation, and it is important to consider changes related to the aforementioned pathologies during physical examination and imaging evaluation.